ANALISIS PENERAPAN ETIKA BISNIS ISLAM DI KEDAI MARTABAK ULAMA INDIA (MUI) TELANAIPURA DI KOTA JAMBI - Alda Fadilla; Efni Anita; Sri Rahma (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This research aims to analyze the implementation of Islamic business ethics at Martabak Ulama India (MUI) Telanaipura in Jambi City. Islamic business ethics is a set of moral principles derived from Islamic teachings that guide businesses to operate ethically and responsibly. This study employs qualitative methods, including observation, interviews, and document analysis. The collected data are analyzed descriptively. The findings from interviews and observations indicate that Martabak Ulama India (MUI) generally adheres to Islamic business ethics. The implementation of Islamic business ethics at Martabak Ulama India (MUI) is evident in various aspects such as not multiplying prices, honesty in measurement, acknowledging product weaknesses and strengths (shiddiq), accountability, providing optimal service, keeping promises (amanah), business communication, ability to convey vision and mission, maintaining good relations with business partners (tabligh), spiritual intelligence, professionalism, and ability to innovate products (fathanah).